2012
DOI: 10.1186/1471-2296-13-77
|View full text |Cite
|
Sign up to set email alerts
|

Stool submission by general practitioners in SW England - when, why and how? A qualitative study

Abstract: BackgroundWe know little about when and why general practitioners (GPs) submit stool specimens in patients with diarrhoea. The recent UK-wide intestinal infectious disease (IID2) study found ten GP consultations for every case reported to national surveillance. We aimed to explore what factors influence GP’s decisions to send stool specimens for laboratory investigation, and what guidance, if any, informs them.MethodsWe used qualitative methods that enabled us to explore opinions and ask open questions through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…The determinants for requesting a faecal specimen, as found by this study, are similar to those found in other studies [28, 3032, 3436] and are consistent with published recommendations on the clinical management of AG cases [4, 37]. Additionally, our study showed that factors related to the health system (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…The determinants for requesting a faecal specimen, as found by this study, are similar to those found in other studies [28, 3032, 3436] and are consistent with published recommendations on the clinical management of AG cases [4, 37]. Additionally, our study showed that factors related to the health system (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Overall response rate within the questionnaire was excellent, as over 94% answered each question bar one where there was a typographical error. The present findings echo the findings of a previous qualitative study, 2 but in a generalisable group of GPs. This survey is reported behaviour and is open to acquiescence bias, and cannot replace a case-based audit or prospective study of clinical cases of diarrhoea; however, such a study would be much more time-consuming.…”
Section: Strengths and Limitationssupporting
confidence: 91%
“…2 This reported behaviour has been backed up by data from a longitudinal study of infectious intestinal disease (IID) in the UK, which showed that there were 147 community cases of IID and 10 GP consultations for every case reported to national surveillance. 3 In the current study, limited but rich qualitative data were used from the previous study, 2 to develop a questionnaire to collect data from a much larger sample of GPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent English survey, 89% of GP responders ( n = 477)21 reported giving verbal advice to patients on how to collect a stool specimen although only 2% gave written instructions;22 this is despite the fact that it has been shown that screening compliance is significantly improved when patients have an information leaflet 23…”
Section: Discussionmentioning
confidence: 99%